A Plastic Substitute for Silicone-Coated Glass Pipettes - Goulian, M (Thrombosis and Haemostasis, 1966)
Directions are given for construction of plastic 0.1 and 0.2 ml pipettes to replace their silicone-coated glass counterparts in blood coagulation work.